The disciples' prayer : the prayer Jesus taught in its historical setting - Gibson, Jeffrey B. (Minneapolis, Fortress Press, 2015)
"What are Christians praying when they pray the 'Lord's Prayer,' and what relationship does it have with Jesus' own context? Jeffrey B. Gibson disputes the view that Jesus' prayer was derived from Jewish synagogal prayers. Understanding its intent requires understanding Jesus' purpose in calling disciples as witnesses against 'this generation.' In context, the prayer was not eschatological and was not aimed at 'calling down' into the present the realities of the 'age to come.' Rather, it was meant to protect disciples from the temptations of their age"--
Preface -- Introduction -- What prayer are we praying when we pray the "Lord's Prayer"? -- What are we praying for when we pray the disciples' prayer? -- What kind of prayer are we praying when we pray the disciples' prayer? -- The prayer's author and his disciples -- Is the disciples' prayer an eschatological prayer? -- The "temptation" petition -- Conclusion -- Appendix. Was John the Baptist the author of the disciples' prayer?
Includes bibliographical references and index
Keywords: Lord's prayer